Borassus aethiopum (Mart.) ethanol fruit extract reverses alloxan-treatment alterations in experimental animals - Moses Dele, Adams; Ejike, Daniel Eze (Mediterranean Journal of Nutrition and Metabolism 15 (2022) 429–44, 2023)
BACKGROUND: Borassus aethiopum fruit is claimed to be used for the management of diabetes without scientific validation. OBJECTIVE: This study seeks to evaluate the antihyperglycaemic activity of ethanol fruit extract of Borassus aethiopum in alloxan-induced diabetic rats. METHODS: 36 rats were placed in six groups (i-vi) (n = 6). Animals in group i (standard) were given 0.4 mls of distilled water (d.w) whereas the ones assigned to group ii, iii, iv, v and vi which were induced into diabetes (by intake of 140 mg/kg body weight [b.w] of alloxan) were also respectively given d.w, 50 mg/kg b.w of metformin, 25, 50 and 100 mg/kg b.w of ethanol fruit extract of Borassus aethiopum, once daily for 14 days. RESULTS: Flavonoid found in the extract (24.04 mg/ml) occurred the most with phenolic (0.35 mg/ml) being the least. While alloxan substantially (p < 0.05) increased the levels of some biological molecules and enzyme activity, it lowered those of others. The extract however significantly (p < 0.05) reversed all the alloxan-induced alterations, with the extract at 100 mg/kg b.w producing figures that compared (p > 0.05) well with those of the d.w treated non-diabetic animals and metformin-treated diabetic animals. The extract also renewed the wholeness of histological damage in the pancreas. CONCLUSION: The bioactive agents of B. aethiopum presented antihyperglycaemic property by preventing diabetes via reversal of alloxan-treatment alterations in the animals